Prosedur Permohonan Bantuan Dana Hibah untuk Pembangunan Tempat Peribadatan di Atas 200 Juta di Biro Kesejahteraan Rakyat Sekretariat Daerah Provinsi Jawa Timur - Fasich Rahman Hendyarta Permana; Kalvin Edo Wahyudi (VISA: Journal of Vision and Ideas, 2024)
The People's Welfare Bureau was formed with the aim of carrying out activities held by the Pusa Government in the form of grant assistance to educational institutions, community groups and places of worship. The Provincial Regional Government as the provincial government administrator can provide social assistance and grants based on Minister of Home Affairs Regulation Number 32 of 2011 (Permendagri Number 32 of 2011) concerning Guidelines for Providing Grants and Social Assistance sourced from the APBD. The People's Welfare Bureau is a distributor of grant aid for institutions or agencies that have applied. However, in real terms, there are still several related institutions or agencies that are still having problems in their administrative processes. The research method used is a qualitative method which aims to determine the role of the Eastern People's Welfare Bureau for national development in Indonesia, especially the construction of selected places of worship and completing procedures in accordance with the existing system. By using indicators of the characteristics of providing social assistance as stated in East Java Governor Regulation No. 44 of 2021 article 30, namely: selective, meeting the requirements for aid recipients and being temporary and not continuous, unless in certain circumstances it can be sustainable, and in accordance with the intended use. The aim of this research is to explain the procedures and flow of grant application from the initial to the final stages.